DETERMINANTS OF GREEN MANAGEMENT PRACTICES IN HOTELS IN KISUMU CITY, KENYA - A THEORETICAL FRAMEWORK - Murimi, Michael (Journal of Strategic Management, 2020)
Purpose: This conceptual paper aims at developing theoretical framework for determinants of green management practices in hotels. Methodology: In order to come up with this theoretical framework, the researcher assumes a process of two phases the first stage will involve an explicit examination green management practices literature and what determines such practices in hotels. The succeeding stage was enhancements of the framework. The theoretical structure relies on the past theoretical explanations and empirical analyses in the fields green management and social sciences. Slack's resource theory and good management competitive theory informs this theoretical framework, the researchers clarify the justification for use of the two theories. Findings: The researcher highlights by what method this reviewed theoretical framework may well be utilized to organize green management practices and its determinants in hotels especially in Kenya. Lastly, the researcher advances propositions that give foundations for empirical study to be carried out in the future. Contribution to theory, practice and policy: Assimilating experiences from numerous disciplines, this paper emphasizes aggregated awareness regarding conceptualization of green management practices in hotels. This work inspires scholars and specialists to understand determinants of green management practices in hotels in Kenya.